Numerical Study for the Effect of Secondary Fluid Inlet Geometrical Parameters on the Performance of Water-Steam Two-Phase Ejector used for Desalination System - Mustafa S. Mahdi; Akram W. Ezzat (Diyala Journal of Engineering Sciences)
This study investigates the effect of secondary fluid inlet geometrical parameters on the performance of a two-phase water-steam ejector operating in the subsonic flow regime. A 3D numerical model, employing the Volume-of-Fluid (VOF) method, was developed to analyze the impact of varying secondary fluid inlet angles (30°, 45°, 60°, 75°, and 90°) and the number of secondary fluid inlets (1, 2, 3, and 4). The study examined these parameters across a range of primary fluid flow rates (6-24 L/min) to understand their interactions. The numerical model was validated through comparison with existing experimental data, demonstrating strong agreement between predicted and measured ejector entrainment ratios (Er). An optimal secondary fluid inlet angle of 45° was identified, providing the best balance between momentum transfer and perpendicular velocity components. It was found also that increasing the number of secondary fluid inlets from 1 to 3 significantly enhanced the ejector Er, while further increases yielded minimal additional improvements. The effects of secondary fluid inlet parameters were more pronounced at higher primary fluid flow rates. These results contribute to a deeper understanding of two-phase ejector performance and provide valuable insights for optimizing their design in various applications.